Penerapan Konsep Deep Learning Dalam Pembelajaran Pendidikan Islam - Gustina, Elvy; M, Iswantir; Wati, Salmi (Institut Agama Islam Sumatera Barat Pariaman, 2025)
This study aims to analyze the application of the deep learning concept in Islamic Religious Education (PAI) and explore the potential and challenges associated with its implementation. Using the literature review method, this research examines relevant literature on deep learning technology, its implementation in education, and how it can be aligned with the Islamic Education curriculum. The findings suggest that deep learning holds great potential to improve the quality of PAI learning through personalized and adaptive learning experiences. However, challenges such as human resource readiness, limited technological infrastructure, and alignment of content with authentic Islamic teachings need to be addressed. This study provides insights into how deep learning can be effectively applied in the context of Islamic Religious Education while maintaining the values and principles of Islamic teachings.